Chirality invertible superstructure mediated active planar optics - Chen, Peng; Ma, Ling-Ling; Hu, Wei; Shen, Zhi-Xiong; Bisoyi, Hari Krishna; Wu, Sai-Bo; Ge, Shi-Jun; Li, Quan; Lu, Yan-Qing (Nature communications, 2019)
Active planar optical devices that can dynamically manipulate light are highly sought after in modern optics and nanophotonics. The geometric phase derived from the photonic spin-orbit interaction provides an integrated strategy. Corresponding elements usually suffer from static functions. Here, we introduce an inhomogeneously self-organized anisotropic medium featured by photo-invertible chiral superstructure to realize geometric phase elements with continuously tunable working spectrum and light-flipped phase profile. Via preprograming the alignment of a cholesteric liquid crystal mixed with a photo-responsive chiral dopant, we demonstrate light-activated deflector, lens, Airy beam and optical vortex generators. Their polychromatic working bands are reversibly tuned in an ultra-broadband over 1000 nm covering green to telecomm region. The chirality inversion triggers facile switching of functionalities, such as beam steering, focusing/defocusing and spin-to-orbital angular momentum conversion. This work offers a platform for advanced adaptive and multifunctional flat optics with merits of high compactness, low loss and broad bandwidth. Optically reconfigurable elements are in demand for future applications. The authors report on the use of chirality-invertible cholesteric liquid crystals to actively manipulate geometric phase and create switchable planar optics elements that perform a variety of functions.